Low temperature CVD of thermoelectric SnTe thin films from the single source precursor, [nBu3Sn(TenBu)]. Issue 3 (23rd December 2020) - Robinson, Fred; Newbrook, Daniel W.; Curran, Peter; de Groot, C. H. (Kees); Hardie, Duncan; Hector, Andrew L.; Huang, Ruomeng; Reid, Gillian
Abstract : [ n Bu3 Sn(Te n Bu)] is an effective precursor for the low temperature growth of continuous SnTe thin films by low pressure CVD; temperature-dependent thermoelectric characterisation of these p-type films is reported. Abstract : This work has demonstrated that the single source precursor [ n Bu3 Sn(Te n Bu)], bearing n -butyl groups and containing the necessary 1 : 1 Sn : Te ratio, facilitates growth of continuous, stoichiometric SnTe thin films. This single source CVD precursor allows film growth at significantly lower temperatures (355–434 °C at 0.01–0.05 Torr) than required for CVD from SnTe powder. This could be advantageous for controlling the surface states in topological insulators. The temperature-dependent thermoelectric performance of these films has been determined, revealing them to be p-type semiconductors with peak Seebeck coefficient and power factor values of 78 μV K −1 and 8.3 μW K −2 cm -1, respectively, at 615 K; comparing favourably with data from bulk SnTe. Further, we have demonstrated that the precursor facilitates area selective growth of SnTe onto the TiN regions of SiO2 /TiN patterned substrates, which is expected to be beneficial for the fabrication of micro-thermoelectric generators.